A case study of students from mixed educational and linguistic backgrounds learning English as a first language in a non-racial school - Leibowitz, Brenda (School of Education, 2016)
This is a case study of a multilingual Standard Nine class in a non-racial Cape Town college, studying English as a first language. It assesses the social and academic effects of the multilingual composition of the class. The study locates the class in the broader South African social and educational context and provides a rationale for emancipatory and reciprocal research. The theoretical foundation for the research methodology, i.e. participant observation, with the teacher as primary observer, is then presented. Theories of Second Language Acquisition (SLA) are discussed in relation to the broader context of language, society and education in South Africa. Arising out of this discussion is a description of progressive English teaching, which is suggested to be appropriate for the multilingual classroom. The prior learning experience of the second language students and the impact of this experience on the second language students in the case study, is illustrated. The social dynamics and level of participation of all students in the classroom, as well as the academic and linguistic development of the second language students. is discussed. The effectivity of the research process itself is assessed. Finally, suggestions for future research and a summary of the findings are presented.